Association of the dopamine β‐hydroxylase 19 bp insertion/deletion polymorphism with positive symptoms but not tardive dyskinesia in schizophrenia. (5th April 2013) - Zhou, Na; Yu, Qiong; Li, Xiaokun; Yu, Yaqin; Kou, Changgui; Li, Wenjun; Xu, Hongqin; Luo, Xingguang; Zuo, Lingjun; Kosten, Thomas R.; Zhang, Xiang Yang
<x xml:space="preserve">Abstract</x> Objective Overactivity of dopaminergic neurotransmission is a putative mechanism of tardive dyskinesia (TD). Dopamine beta‐hydroxylase (DBH) is a key enzyme in the conversion of dopamine to norepinephrine, and plasma DBH activity is altered in TD patients. This study examined whether the functional DBH 5'‐Ins/Del polymorphism was associated with TD severity in Chinese patients with schizophrenia. Methods We compared the rate of this polymorphism in patients with (n = 312) and without TD (n = 435), and healthy controls (n = 625). The severity of TD was assessed using the Abnormal Involuntary Movement Scale (AIMS) and psychopathology using the Positive and Negative Syndrome Scale (PANSS). Results There were no significant differences in the distribution of the allele and genotype frequencies between the patients and controls, or between the patients with and without TD. Also, there was no significant difference in the AIMS total score between the three genotype groups. However, the PANSS positive symptom subscore was significantly higher in patients with Del/Del genotype (13.2 ± 5.2) than those with Ins/Del (11.2 ± 4.9) and Ins/Ins (11.1 ± 3.1) genotypes (both p < 0.05). Conclusion These results suggest that although the DBH 5'‐Ins/Del polymorphism was not associated with susceptibility to TD in patients with schizophrenia, it might be related to positive symptoms of schizophrenia. Copyright © 2013 John Wiley & Sons, Ltd.